A Longitudinal Mixed-Methods Examination of Positive Health Check: Implementation Results From a Type 1 Effectiveness-Implementation Hybrid Trial. (1st September 2022) - Garner, Bryan R.; Burrus, Olivia; Ortiz, Alexa; Tueller, Stephen J.; Peinado, Susana; Hedrick, Haley; Harshbarger, Camilla; Galindo, Carla; Courtenay-Quirk, Cari; Lewis, Megan A.
Abstract : Background: Positive Health Check is an evidence-based video doctor intervention developed for improving the medication adherence, retention in care, and viral load suppression of people with HIV receiving clinical care. Setting: Four HIV primary care clinics within the United States. Methods: As part of a type 1 hybrid trial, a mixed-methods approach was used to longitudinally assess the following 3 key implementation constructs over a 23-month period: innovation-values fit (ie, the extent to which staff perceive innovation use will foster the fulfillment of their values), organizational readiness for change (ie, the extent to which organizational members are psychologically and behaviorally prepared to implement organizational change), and implementation climate (ie, the extent to which implementation is expected, supported, and rewarded). Quantitative mixed-effects regression analyses were conducted to assess changes over time in these constructs. Qualitative analyses were integrated to help provide validation and understanding. Results: Innovation-values fit and organizational readiness for change were found to be high and relatively stable. However, significant curvilinear change over time was found for implementation climate. Based on the qualitative data, implementation climate declined toward the end of implementation because of decreased engagement from clinic champions and differences in priorities between research and clinic staff. Conclusions: The Positive Health Check intervention was found to fit within HIV primary care service settings, but there were some logistical challenges that needed to be addressed. Additionally, even within the context of an effectiveness trial, significant and nonlinear change in implementation climate should be expected over time.